2015
DOI: 10.1002/srin.201400117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MnO and CaO/SiO2Mass Ratio on Phase Formations of CaOAl2O3MgOSiO2CrOxSlag at 1673 K and PO2=10−10 atm

Abstract: The knowledge on distribution of mineralogical phase in slag is of vital importance to disposal and utilization of slag. Despite of certain amount (up to 5%) of MnO found in stainless steel slag, MnO distribution in phases of slag was not thoroughly investigated. In this work, phases of synthetic CaO–Al2O3–MgO–SiO2–CrOx–MnO slag with varied CaO/SiO2 and MnO content, which was soaked at 1673 K for 12 h, were determined by combining SEM‐EDS and XRD technique. Phases for samples with CaO/SiO2 ratio of 1.5 and 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…[9] Albertsson et al [10,11] indicated that slow cooling, low oxygen partial pressure and low slag basicity (1.0 to 1.4) can improve the spinel phase precipitation. Shu et al [12] found that the size of the spinel phase increased with increasing MnO content and decreasing CaO/SiO 2 ratio. However, disintegration was found in samples with a high MnO content and CaO/ SiO 2 ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Albertsson et al [10,11] indicated that slow cooling, low oxygen partial pressure and low slag basicity (1.0 to 1.4) can improve the spinel phase precipitation. Shu et al [12] found that the size of the spinel phase increased with increasing MnO content and decreasing CaO/SiO 2 ratio. However, disintegration was found in samples with a high MnO content and CaO/ SiO 2 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Hence, the immobilization of chromium in stainless steel slag has been investigated by many researchers. [8][9][10][11][12][13][14][15] Romero-Serrano et al [8] reported that chromium leaching was suppressed by adding MgO to the CaO-SiO 2 -Cr 2 O 3 system, which was attributed to stable binding of chromium in the MgCr 2 O 4 phase. They also found that the addition of FeSO 4 and FeS 2 had positive effects on the immobilization of chromium.…”
Section: Introductionmentioning
confidence: 99%
“…The mitigation of disintegration of slag could be achieved by some physical methods, such as rapid cooling to suppress the phase transition [3]. The modification of slag could be performed by additives to mitigate the disintegration of slag and immobilize chromium in slag [4][5][6][7][8][9]. It is well accepted that spinel phase is very stable during oxidation and leaching due to the strong bonding of chromium in spinel phase [2].…”
Section: Introductionmentioning
confidence: 99%
“…Modification with MgO could mitigate the precipitation of Ca 2 SiO 4 [4] and be beneficial to spinel formation during solidification of slag [5,6]. The additions of appropriate amounts of Al 2 O 3 [5,7], MnO [8], and FeO [9] were found to promote the spinel formation. Meanwhile, low basicity [6,8,10] and oxygen partial pressure [11] have a positive influence on spinel precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation